TUBERCULOSIS AND ENVIRONMENTAL POLLUTION IN IVANO-FRANKVSK REGION - Зозуляк, В. І.; Зозуляк, Н. В.; Зозуляк, З. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The aim – to examine the prevalence and characteristics ecoindastial pollution and epidemiological indicators of tuberculosis in the Carpathian region. Materials and methods. The basis of the study of materials used reports Ivano-Frankivsk Regional phthisiopulmology center, epidemiological indicators of tuberculosis for 2011-2012 years: the overall incidence, morbidity lung disease destructive tuberculosis, the proportion of cavities, the incidence of mycobacteriumexcretion, disease of adolescents and children mortality in some districts. We also used the background monitoring of pollution of the biosphere, soil, air and water. Results and discussion. The obtained results of epidemiological studies and data of medical statistics clearly confirm the trend towards deterioration in health, as well as increased morbidity and mortality from tuberculosis in contaminated areas in the Carpathian region. Adverse environmental factors and high levels of anthropogenic pollution lead to a disruption in the body’s antioxidant system, which in turn can run multiple mechanisms of tuberculous process, increases the incidence of functional disorders of the liver. Conclusions. The tendency of the relationship ecoindastial pollution and improving epidemiological indicators of tuberculosis in parts of Carpathians.